Historyczne i współczesne postawy wobec śmierci - Wojciech Bołoz (Studia Ecologiae et Bioethicae)
Though death is a universal and real event, large diversity of the attitudes to death are observed. Depending on the culture and historical period, death has been perceivable as distant and horrible, or mysterious and fascinating. In the last years in the area of western civilization the increased interest in this issue occurred. Attempt has been made to consider death as one of the events of human life, which is present in both individual and social consciousness. Relegation of tanatological issues into subconsciousness or passing them over does not eliminate the confrontation with this important existential problem. The analysis of historical attitudes to death can help to avoid in our time mistakes, which in the past were making most often.